CORNUCOPIA OF CULTURED SCHWANN CELLS: WHERE IS THE BEST SOURCE IN ALBINO RATS? - MIRAJULLAH, M.; XINYA, SHEN; AIDONG, LIU C; Yujiang, Wang (Journal of Ayub Medical College Abbottabad, 2001)
Background: Schwann Cells (SC) arc multifunctional glia cells with diversified biological potentials. To study their biological activities, ample amount of cultured SC is a pre-requisite. Many sources have been exploited in the past for SC culture but unfortunately no attempt has been made to find the richest source. Methods: To make an attempt in this direction, we cultured SC under identical conditions from various neural sites in the neonate & young SD albino rats. Fresh, cryopreserved & pre-stimulated neural tissue- have been compared for total & % of SC/unit tissue from the combined data of living & immunostained cultures Results: Our data shows that the upper limb nerves have not only quantitative advantage (2.35x104 cells/rng tissue) but also have significant qualitative edge (P< .05- .01) over the remaining sources. It can be concluded from our data that upper limb nerves are the best available source for SC/unit tissue.